Exploring The Impact of Discipline Training at Yonif 328 Dirgahayu Military Barracks on Young Adults Behavioral Transformation: “A Qualitative Study" - Utami, Diah; Nurrela, Nisa; Maharani, Sella Sakilla; Rukmana, Ovalia (Dinasti International Journal of Education Management and Social Science, 2025)
This study explores the impact of discipline training conducted in a military barrack setting on young adults behavioral transformation in response to rising juvenile delinquency and weakening personal discipline among Indonesian youth, particularly in Depok, West Java. The program, implemented by Yonif Dirgahayu 328, incorporates physical training, national value reinforcement, and structured character development within a disciplined, regimented environment. Implementing a qualitative phenomenological approach, the study examines how this intervention shapes responsibility, leadership, and patriotism among young adults aged 13–15. Data were gathered through semi-structured interviews, focus group discussions, and participant observation involving students, parents, teachers, military instructors, and program coordinators. Thematic analysis identified notable behavioral changes such as improved time management, greater respect for authority, enhanced collaboration, and emotional regulation. Despite these gains, participants faced challenges in sustaining disciplined behavior post-program, particularly when returning to unsupportive home or school environments. The findings underscore the importance of sustained reinforcement from families and educational institutions to ensure long-term internalization of the values instilled during the training. While discipline in a military barrack presents a promising alternative for character education, its effectiveness relies on adaptive, collaborative support systems involving educators, caregivers, and policy stakeholders.